1882 Ga. Laws 131 - (:unkn) unknown (My University, 1882)
An Act to Prevent the Discharge of Fire-arms on the Public Highways of this State and within Fifty Yards of the Same; to make such an act a Misdemeanor, and Prescribe a Punishment Therefor, § 1: Prohibited wantonly discharging a gun or pistol between the "dark and daylight" on any of the public highways or within fifty yards of such public highways.
Keywords: DISCHARGE